2003
DOI: 10.1038/sj.bmt.1703782
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic chemotherapy preceding apheresis of peripheral blood progenitor cells can affect the early reconstitution phase of naive T cells after autologous transplantation

Abstract: Summary:Transient T cell immunodeficiency is a common complication following hematopoietic stem cell transplantation. In breast cancer patients transplanted with autologous peripheral blood progenitor cells (PBPC) harvested after cytotoxic treatment with either cyclophosphamide or epirubicin plus paclitaxel, we evaluated T cells infused in grafts and in peripheral blood during the early reconstitution phase. We found that PBPC grafts harvested after treatment with epirubicin plus paclitaxel contained substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…Interestingly, the analysis of the immune reconstitution period revealed that a single cycle of Busulfan and Fludarabine particularly depleted CD8 + T-cells, resulting in increased CD4/CD8 ratios followed by a slow recovery compared with the CD4 + subset. This is in contrast with previous reports of marked depletion CD4 + T-cells for several months with decreased CD4/ CD8 ratios <1 and clinical immunosuppression, 15,[25][26][27][28][29] although lymphodepletion in these studies was usually induced by the use of cyclophosphamide (CTX) in a transplant setting. Data from preclinical, in vitro analyses indicate that the treatment of PBMCs with Fludarabine leads to a higher level of apoptosis in CD8 + T-cells compared with CD4 + T-cells.…”
Section: Discussioncontrasting
confidence: 81%
“…Interestingly, the analysis of the immune reconstitution period revealed that a single cycle of Busulfan and Fludarabine particularly depleted CD8 + T-cells, resulting in increased CD4/CD8 ratios followed by a slow recovery compared with the CD4 + subset. This is in contrast with previous reports of marked depletion CD4 + T-cells for several months with decreased CD4/ CD8 ratios <1 and clinical immunosuppression, 15,[25][26][27][28][29] although lymphodepletion in these studies was usually induced by the use of cyclophosphamide (CTX) in a transplant setting. Data from preclinical, in vitro analyses indicate that the treatment of PBMCs with Fludarabine leads to a higher level of apoptosis in CD8 + T-cells compared with CD4 + T-cells.…”
Section: Discussioncontrasting
confidence: 81%
“…Thus, the dynamics of T-cell are very sensitive to the dose of GC [4,37,42,63,64]. Hence, an optimal level of GC administration is essential for the proper functioning of the human body.…”
Section: Resultsmentioning
confidence: 99%
“…Since transient T cell immunodeficiency is a common complication following hematopoietic stem cell transplantation, rescue of T cell function by autologous T cells was expected to be beneficial for immunotherapeutic approaches [5]. In our own pilot study for MBC, this immunotherapeutic approach was included into the HDCT protocol (Fig.…”
Section: Discussionmentioning
confidence: 99%